The economics of beer - Swinnen, Johan (Oxford University Press, 2011)
Beer was the drink of choice in many ancient societies and throughout the past centuries in large parts of the world. Right now, it is globally by far the most important alcoholic drink, in volume and value terms. The largest brewing companies have developed into global multinationals. The beer market is characterized by strong growth in emerging economies, by a substantial decline of (per capita) beer consumption in traditional markets, and a shift to new products. There has been a strong interaction between governments (politics) and markets (economics) in the beer industry. For centuries, taxes on beer or its raw materials were a major source of tax revenue for governments. Governments have also regulated the beer industry for reasons related to quality, health, and competition. The beer market is not only an interesting sector to study in itself but also yields important general economic insights. This book is the first economic analysis of the beer market and brewing industry. It comprises a comprehensive and unique set of economic research and analysis on the economics of beer and brewing. The various chapters cover economic history and development, demand and supply, trade and investment, geography and scale economies, technology and innovation, health and nutrition, quantity and quality, industrial organization and competition, taxation and regulation, and regional beer market developments.